Public Sector Contracting Model for Management of Construction Tender Price Volatility - moffat tembo; Charles Kahanji; Erastus Misheng’u Mwanaumo (Journal of Construction Project Management and Innovation)
Construction tender price volatility threatens desirable infrastructure push in the public sector. The damaging effects of escalating tender prices outweigh the socioeconomic benefits of such infrastructure. If not addressed, this harmful effect destroys construction sector productivity, causing it to lag behind other economic sectors, thereby decreasing its value in the national economy. Contractors use price to mitigate procurement and client-related risks at the tendering stage. The trend requires developing and implementing procurement strategies that consider price control implications at the project tendering phase, leading to the development of contract delivery models that inadequately address the impact and potential value of pricing in construction projects. This research focuses on implementing procurement strategies by developing a public sector contracting model considering price reduction implications at the project tendering phase. The study investigates pricing behaviours regarding implementing current contracting delivery models in Zambia and develops a conceptual model for managing tender price variability in the public construction sector. The study achieved this through a comprehensive literature review followed by semi-structured interviews with 14 purposively and snowball-sampled industry experts. The study utilises person-to-person interviews to collect data from interviewing 14 purposive identified respondents to attain relevant research results. The findings show that governments can maximise social gains from an infrastructure project by deriving accurate technical parameters and optimising procurement. The study identifies four pricing behaviours demonstrated by contractors during tendering: resistance, reactive, anticipatory, and Consultant-based. Consultant-based pricing was the least practised behaviour, whereas reactive was the most established among all behaviours. Emergent patterns for turnaround strategies include cost estimating and financing, mitigating external and internal interferences, providing incentives, providing training, and encouraging innovations. Others include revising legislation, contextualising procurement functions, improving project management practices, predicting market forces, and guaranteeing sustainability. The study further proposes the conceptual Negotiated Construction Approach (NCA) for public projects that summarises and weaves together identified strategies.